Healthcare analytics : foundations and frontiers - Mullner, Ross M.; Rafalski, Edward M. (Routledge, Taylor & Francis Group, 2020)
This is a comprehensive, practical guide which looks at the advantages and limitations of new data analysis techniques being introduced across public health and administration services. The Affordable Care Act (ACT) and free market reforms in healthcare are generating a rapid change of pace. The "electronification" of medical records from paper to digital, which is required to meet the meaningful use standards set forth by the Act, is advancing what and how information can be analyzed. Coupled with the advent of more computing power and big data analytics and techniques, practitioners now more than ever need to stay on top of these trends. This book presents a comprehensive look at healthcare analytics from population data to geospatial analysis using current case studies and data analysis examples in health. This resource will appeal to undergraduate and graduate students in health administration and public health. It will benefit healthcare professionals and administrators in nursing and public health, as well as medical students who are interested in the future of data within healthcare.
Keywords: Medical informatics.; Medicine -- Data processing.; Medical Informatics; Medical Informatics Applications; Médecine -- Informatique.; MEDICAL -- Public Health.; Medicine -- Data processing; Medical informatics